PERGESERAN KEKUASAAN LEMBAGA NEGARA PASCA AMANDEMEN UUD 1945 - Sri Nur Hari Susanto (Masalah-Masalah Hukum, 2014)
Amendments (changes) of the 1945 Constitution in principle to change the constitutional system has adopted and implemented in Indonesia. Consequences of state structure system change, lead to a change of position, authority and ways of charging state agencies. The change set is governed by the Constitution, into law the existence of state institutions, raises problems of relations between state institutions, because there are powers that can be implemented independently and there is to be implemented in conjunction with other state agencies